Motif keusahawanan: Kajian usahawan Melayu Daerah Pendang Kedah Darul Aman - Abdul Hamid, Solahuddin; Dahaman@Dahlan, Mohd Akram (Universiti Utara Malaysia, 2014)
The Malay community is often described as not interested in a career as an entrepreneur.If given a choice, they are assumed to prefer conventional careers such as working with the government and went into politics.Among the entrepreneurs, they are said to have less behavioral characteristics of an entrepreneur.The question is whether these negative elements can be generalized to the whole of Malay community? In the context of a pluralistic society, a variety of negative stereotypes is very dangerous if it is attributed to the whole of Malay community.In the context of spirituality, the image of syumul in Sharia is generally contaminated because the Malays in this country are Muslim.This study examines the motives that influence the Malay entrepreneurship regardless of the form and scale of their business.Researcher have classified priority to motivation entrepreneurship religious motives, gain a position in the community, personal development, as well as the desire to gain freedom and guarantee.The focus of personality in this study involved only among entrepreneurs around daerah Pendang, Kedah only. The majority of respondents chose the religious motivation as their motives involved in entrepreneurship.These findings are in line with the aspirations, patterns of thinking and value system of Islam and social structure are very encouraging balanced economic development with spiritual development.